THE INFLUENCE OF HYBRID LEARNING ON STUDENT MOTIVATION AND ACHIEVEMENT IN THE DIGITAL ERA - Shinta Dzauharoh; Silvia Ekasari; Sufia Widi Kasetyaningsih (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This research focuses on a comprehensive literature analysis on the effect of hybrid learning on students' motivation and learning achievement. Through the literature research method, this study collects, reviews and analyses relevant scholarly works from journals, books, conferences and other academic sources. The results show that hybrid learning, when designed by effectively blending face-to-face and online elements, can increase students' motivation by giving them more control over their learning process. This not only helps in meeting students' individual needs but also in encouraging a sense of responsibility for their own learning. In the context of learning achievement, hybrid learning is proven to deliver positive results, especially when accompanied by strong pedagogical support and active participation from students. Conclusions from the literature analysis emphasise the importance of the teacher's role in designing and implementing hybrid learning to maximise its benefits on students' motivation and academic achievement. This research provides important insights for educational practitioners and policy makers on how hybrid learning can be optimised to support successful educational attainment.